Digestibility of Broiler Birds Fed Degraded and Detoxified Delonix Regia (Global Journal of Science Frontier Research, 2020)
In an experiment to study the digestibility of broiler birds fed degraded and detoxified Delonix regia (DDD), 180 broiler birds fed DDD for eight (8) weeks and at the end of the experiment, it was found that dry matter, protein, ether extract and crude fibre decreases with increase in DDD.